n-alkane profiles of lard and vegetable oils, and their chemometric differentiation - Nur Ain Syaqirah Sapian; Muhamad Aidilfitri Mohamad Roslan; Amalia Mohd Hashim; Yanty Noorzianna Abdul Manaf; Mohd Nasir Mohd Desa; Murni Halim; Muhamad Shirwan Abdullah Sani; Mohd Termizi Yusof; Mohd Sabri Pak Dek; Helmi Wasoh (Malaysian Palm Oil Board, 2024)
This research aims to examine fat from various vegetable oils using n-alkane profles, as well as chemometrics and machine learning. Unsaponifable vegetable oils (coconut, peanut, palm and soybean oils) were separated and analysed using gas chromatography-mass spectrometry (GC-MS) to investigate the n-alkane profles of each fat. The authenticity of the detected n-alkane profles was determined by comparing to the retention time of C7 -C40 n-alkane standards. The test designs were developed using Principal Component Analysis (PCA), Hierarchical Clustering Analysis (HCA), Partial Least Squares-Discriminant Analysis (PLS-DA), and Random Forest (RF). Both PCA and HCA appeared to provide a clear distinction between each of the vegetable oil tests. Based on the PLS-DA and RF determination, tetracosane (C24) and octadecane (C18) are proposed as the key n-alkane markers for separating lard from vegetable oils. These fndings suggest that additional work may be required to achieve and determine the diferent characteristics across oils in numerous statistical applications, notably chemometrics and machine learning.